Calculate the pay for the following day of a weekly time card given a wage of \$13/hr . Name Week of Morning In Out Monday 08:00 12:15 Afternoon in Out 13:00 17/15 pay = $ [ ? ] Round your answer to the nearest hundredth

Skip to content# Calculate the pay for the following day of a weekly time card given a wage of $13/hr . Name Week of Morning In Out Monday 08:00 12:15 Afternoon in Out 13:00 17/15 pay = $ [ ? ] Round your answer to the nearest hundredth

Mathematics ##
Comments (3) on “Calculate the pay for the following day of a weekly time card given a wage of $13/hr . Name Week of Morning In Out Monday 08:00 12:15 Afternoon in Out 13:00 17/15 pay = $ [ ? ] Round your answer to the nearest hundredth”

### Leave a Reply Cancel reply

Calculate the pay for the following day of a weekly time card given a wage of \$13/hr . Name Week of Morning In Out Monday 08:00 12:15 Afternoon in Out 13:00 17/15 pay = $ [ ? ] Round your answer to the nearest hundredth

c 1 hour

step-by-step explanation:

m = 2e

m = 2 so 2 = 2e

1 = e

hey, um i need your help with something ill answer your question if u brainlist me on this coz the thing is their gonna ban me if i dont get 10 brainlist in 2 weeks, pls help a stranger out. ill owe u!! and im so worried because i have heaps of work thats due i really need this please.

(0,-3) see attached graph

step-by-step explanation:

a. to solve the system, graph the two equations.

x = y+3 becomes y=x-3 has m=1/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move up 1 unit and 1 unit to the right. plot a point and connect.

y=-4x+3 has m =-4/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move down four units and to the right 1 unit. plot a point and connect.

the solution is the point (x,y) where the two lines intersect. by the graph below it is (0,-3).

b. to solve by substitution, substitute y = -4x-3 into x= y+3

x= (-4x-3) +3

x=-4x

5x=0

x=0

now substitute x = 0 back in to find y.

y= -4(0)-3

y=0-3

y=-3

solution is (0,-3)

c. use elimination by adding the equations together.

x-y=3

4x+y=-3

5x=0

x=0

then substitute into one equation to find y.

y=-4(0)-3

y=-3